The EMBRACE Trial: Prolonged Ambulatory Cardiac Monitoring Improves the Detection and Treatment of Atrial Fibrillation in Patients with Cryptogenic Stroke - Vinall, Phil (MD Conference Express, 2013)
Data from the 30-Day Cardiac Event Monitor Belt for Recording Atrial Fibrillation After a Cerebral Ischemic Event trial [EMBRACE; NCT00846924] showed that prolonged continuous cardiac monitoring to detect poststroke paroxysmal atrial fibrillation in patients with unexplained strokes is feasible, more effective than standard approaches, and leads to clinically meaningful changes in patient management.